Shakespearean Remakes in Recent Russian Drama - Шамина, Вера Б. (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
The article addresses postmodern plays by recent Russian playwrights, which use the plot of Shakespeare’s Hamlet, such as L. Petrushevskaya, B. Akunin, V. Korkiya and brothers Presnyakov. It demonstrates different techniques and approaches they use to deconstruct the original text. In the end the author comes to the conclusion that these playwrights in their games with classics to a great extent follow the path that was laid by the Bard himself.